The Future of Agri-food Systems in Central West Asia and North Africa (CWANA) - Frija, Aymen; Cenacchi, Nicola (International Center for Agricultural Research in the Dry Areas, 2024)
The objective of this brief is to provide a comprehensive review of the primary foresight studies that concentrate on the future of agri-food systems in Central and West Asia and North Africa (CWANA). It aims to present the key findings and recommendations from these studies. The identification of gaps in foresight to enhance comprehension of future dynamics, drivers, challenges, impacts, and key transformations has also been undertaken, and the brief proposes avenues for future research and action.